Relationship between peak spatial-averaged specific absorption rate and peak temperature elevation in human head in frequency range of 1-30 GHz - Morimoto, Ryota; Laakso, Ilkka; De Santis, Valerio; Hirata, Akimasa (Physics in medicine & biology, 2016)
This study investigates the relationship between the peak temperature elevation and the peak specific absorption rate (SAR) averaged over 10 g of tissue in human head models in the frequency range of 1-30 GHz. As a wave source, a half-wave dipole antenna resonant at the respective frequencies is located in the proximity of the pinna. The bioheat equation is used to evaluate the temperature elevation by employing the SAR, which is computed by electromagnetic analysis, as a heat source. The computed SAR is post-processed by calculating the peak spatial-averaged SAR with six averaging algorithms that consider different descriptions provided in international guidelines and standards, e.g. the number of tissues allowed in the averaging volume, different averaging shapes, and the consideration of the pinna. The computational results show that the SAR averaging algorithms excluding the pinna are essential when correlating the peak temperature elevation in the head excluding the pinna. In the averaging scheme considering an arbitrary shape, for better correlation, multiple tissues should be included in the averaging volume rather than a single tissue. For frequencies higher than 3-4 GHz, the correlation for peak temperature elevation in the head excluding the pinna is modest for the different algorithms. The 95th percentile value of the heating factor as well as the mean and median values derived here would be helpful for estimating the possible temperature elevation in the head.